(untitled) (Scottish Historical and Archaeological Internet Reports, 2021)
The extensive remains of enclosed and unenclosed prehistoric settlements, including the remains of at least 14 circular structures, were discovered within ten areas of archaeological interest, situated on well-drained knolls in an undulating landscape north of Blackford village. The settlements have been dated principally to the Middle and Late Bronze Age, although continued habitation can be traced through to the Early Iron Age. Most of the structures were probably roundhouses, and were likely to have been the foci of domestic and economic life across generations. The remains ranged from single isolated structures to groups of closely spaced structures. Some were enclosed by palisades, possibly for defence, others were not. Diachronic changes in architecture are readily identifiable. The community made their living from a mixed farming economy, with some craft production also undertaken. Evidence for funerary rites was rare, but what little there was suggests that the dead were cremated and buried in urns.